Sheilas: 28 Years On - Goldson, Annie; Hutchesson, Dawn (New Zealand, 2004)
Verzio FF submission The film features the stories of five prominent New Zealand second wave feminists who first appeared on our television screens in 1977, in the controversial feminist documentary series Women. In Sheilas: 28 Years On contemporary interviews with the women about their lives and their political beliefs are juxtaposed with archival footage from the original series and from the 1960s to the 1980s. This provides a visual background to what motivated the women to become politically active and documents the changes that have occurred as a result of their activism, both in their own lives and in New Zealand society. Students will gain insight into the causes and consequences of second wave feminist activism in New Zealand through viewing the film.